Septum Perforation in a Patient with Asymptomatic Systemic Lupus Erythematosus - Akbari Dilmaghani, Nader; Peyvandi, Maryam; Zangane, Ali; Moradi, Leila (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2021)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease in which organs and cells are damaged by autoantibodies and immune complexes. This disease often affects the body organs, one of which is the vascular system that manifests itself as vasculitis. Rarely, this vasculitis can cause perforation and epistaxis in the nasal septum. Most people who present this manifestation in lupus are people who have a known lupus case and develop septal perforation over time. Case Presentation: In this article, a patient with epistaxis and septal perforation was referred and, finally, she was diagnosed with lupus. Conclusion: This study shows that other than granulomatous and eosinophilic angiitis (Wegner & Churg-Strauss), systemic lupus erythematous should be in mind in diagnosis of septal perforation.